Degradasi Sampah Biomassa dengan Bioaktivator EM4 sebagai Bentuk Pengendalian Limbah di Desa Neuheun - Lubis, Mirna Rahmah; Fathanah, Umi; Rosnelly, Cut Meurah; Aflah, Nurul (Universitas Nusantara PGRI Kediri, 2021)
Waste that is not managed properly in Neuheun Village, Aceh Besar Regency, can cause health and environment problems. Therefore, this service activity aims to provide the people of Neuheun village with the knowledge and skills of making organic fertilizer in a simple way. The fertilizer making is carried out through short training with raw materials that are reachable by the village community. The target of theses activities is housewives in the village, the majority of whom do not work and spend their time taking care of the household. Apart from filling the time, this activity can add insight, self-efficacy, and improve family health and economic life. These activities were attended by 20 housewives who are members of the recitation of the women of Neuheun Village. These activities take place through counseling and direct training stages. Counseling was provided through the distribution of reading materials and delivery of materials followed by the organic fertilizer making. The evaluation results show the enthusiasm of the participants in participating in the training, and they are able to make organic fertilizer. Making fertilizer is expected to be a side business and increase public knowledge about the benefits of organic fertilizers.